ANALISIS VEGETASI KEANEKARAGAMAN ANGGREK EPIFIT DI HUTAN BEKAS TEBANGAN, HUTAN PENELITIAN MALINAU (MRF) – CIFOR (Vegetation Diversity Analysis of Orchid Epiphytes at the Logged Over Forest of Malinau Research Forest (MRF) – CIFOR) - Akas Pinaringan Sujalu (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
The objective of this research was to identify various kinds of Orchidaceae epiphytes and their porophyte in the logged over forest of 12 hectares within Malinau Research Forest (MRF-CIFOR) Seturan – Ddistrict of Long Loreh, Malinau.Regency. The research found 37 species with 2, 4 individual orchids epiphytes at each phorophyte. The Bulbopphyllum beccariu Rchb.f. is the most one orchids epiphytes at the crown and at the bark trees.The Dominant Index Species (C) at the crown ,.04141 and at the bark 0,34551. The Various Index of Species (H) at the crown 1,3801 and at the bark 0,46975. The Similarity Index of spcies from Shφrensen(ISs) at the crown 16,22.Keywords: Orchidaceae epiphytes, diversity, similarity